2010
DOI: 10.3109/00365521.2010.516452
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of omentin, chemerin and adipsin in patients with biopsy-proven nonalcoholic fatty liver disease

Abstract: Our results suggest that serum omentin levels are raised in patients with NAFLD regardless of potential confounders and represent an independent predictor of hepatocyte ballooning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 28 publications
6
112
2
1
Order By: Relevance
“…Studies have shown that omentin-1 levels are usually reduced in patients with IR, but there are some different findings in the literature. Yilmaz et al 35 reported that omentin-1 was significantly increased in patients with nonalcoholic fatty liver disease in which IR is highly prevalent. Furthermore, treatment with metformin and pioglitazone, insulin sensitizing drugs, reduced the levels of omentin-1 in patients with newly diagnosed diabetes in spite of the fact that a significant improvement in HOMA-IR were found in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that omentin-1 levels are usually reduced in patients with IR, but there are some different findings in the literature. Yilmaz et al 35 reported that omentin-1 was significantly increased in patients with nonalcoholic fatty liver disease in which IR is highly prevalent. Furthermore, treatment with metformin and pioglitazone, insulin sensitizing drugs, reduced the levels of omentin-1 in patients with newly diagnosed diabetes in spite of the fact that a significant improvement in HOMA-IR were found in another study.…”
Section: Discussionmentioning
confidence: 99%
“…An association of circulating chemerin levels with the markers of NAFLD has also been highlighted, but the results have been inconsistent in terms of some of the investigated histological features (28,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…We detected that omentin levels are increased with loss of weight contrary to literature. NAFLD may be a confounder; so that, we suggest additional studies to identify reasons for this paradoxical increase as proposition of Yılmaz et al (26).…”
Section: Methodsmentioning
confidence: 80%
“…Reduced omentin levels in patients with diabetes are also observed (24,25). Interestingly, Yılmaz et al showed that serum omentin levels are raised in patients with NAFLD, omentin levels are positively associated with hepatocyte ballooning -indicator of hepatocyte degeneration-independent of insulin resistance and some features of the metabolic syndrome (26). They also hypothesized that omentin might play a role in the development and progression of NAFLD.…”
Section: Methodsmentioning
confidence: 98%